Electric field-induced chiral d+id superconductivity in AA-stacked bilayer graphene: a quantum Monte Carlo study. (15th October 2020) - Fang, Shi-Chao; Zheng, Xiao-Jun; Lin, Hai-Qing; Huang, Zhong-Bing
Abstract: Using the constrained-path quantum Monte Carlo method, we systematically study the half-filled Hubbard model on AA-stacked honeycomb lattice. Our simulations demonstrate that a dominant chiral d + id wave superconductivity can be induced by a perpendicular electric field. At a fixed electric field, the effective pairing interaction of chiral d + id superconductivity exhibits an increasing behavior with increasing the on-site Coulomb interaction. We attribute the electric field-induced d + id superconductivity to an increased density of states near the Fermi energy and robust antiferromagnetic spin correlation upon turning on electric field. Our results strongly suggest that the AA-stacked graphene system is a good candidate for chiral d + id superconductor.